Silicon VLSI technology : fundamentals, practice, and modeling - Plummer, James D. (Prentice Hall electronics and VLSI series, 2000)
Unique in approach, this book provides an integrated view of silicon technology--with an emphasis on modern computer simulation. It describes not only the manufacturing practice associated with the technologies used in silicon chip fabrication, but also the underlying scientific basis for those technologies. Modern CMOS Technology. Crystal Growth, Wafer Fabrication and Basic Properties of Silicon Wafers. Semiconductor Manufacturing--Clean Rooms, Wafer Cleaning and Gettering. Lithography. Thermal Oxidation and the Si/SiO2 Interface. Dopant Diffusion. Ion Implantation. Thin Film Diffusion. Etching. Backend Technology. For anyone interested in Fabrication Processes.